TEACHERS’ TRAINING BY DISTANCE TEACHING METHOD: THE 15-YEAR EXPERIENCE AT KAUNAS UNIVERSITY OF TECHNOLOGY - Bankauskienė, Nijolė; Masaitytė, Ramunė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The modern epoch raises greater and greater requirements for teachers’ competence and qualification. So a pedagogue is obliged to constantly develop them. For 15 years Kaunas University of Technology has already provided teacher training by distance teaching method. In order to achieve the aim it has modern technical base and the teacher training programme “Pedagogical Studies”. Considering the time and its requirements the programme content also changed. This article reviews the content and its change of the teacher training programme.